2021
DOI: 10.1021/acs.jpca.1c01653
|View full text |Cite
|
Sign up to set email alerts
|

Gauge Dependence of the Molecular Orbital Space Decomposition of Optical Rotation

Abstract: Optical rotation (OR) is a foundational technique for the detection and characterization of chiral molecules, but it is poorly understood how the observed property relates to the structure of the molecule. Over the years, several schemes have been developed to decompose the OR into more chemically intuitive contributions. In this paper, we introduce two alternative formulations of our previously developedS molecular orbital space decomposition. These new expressions use the Modified Velocity Gauge-Magnetic (MV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 39 publications
(93 reference statements)
0
13
0
Order By: Relevance
“…Grimme et al suggested a simplified TDDFT (sTDDFT), which is so cheap to allow many calculations on several snapshots taken from a preliminary molecular dynamics (MD) 8 calculation, or an automated procedure to treat flexible molecules 9 . From a different perspective, Caricato et al have studied the problem of the gauge choice in optical rotation 10–14 . Mennucci et al worked on excitonic models 15 while Cappelli on the chiroptical properties in aqueous solution 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Grimme et al suggested a simplified TDDFT (sTDDFT), which is so cheap to allow many calculations on several snapshots taken from a preliminary molecular dynamics (MD) 8 calculation, or an automated procedure to treat flexible molecules 9 . From a different perspective, Caricato et al have studied the problem of the gauge choice in optical rotation 10–14 . Mennucci et al worked on excitonic models 15 while Cappelli on the chiroptical properties in aqueous solution 16 .…”
Section: Introductionmentioning
confidence: 99%
“…The latter can then be used for a detailed analysis of the electron density redistribution for these relevant transitions as done in our previous studies. 1,[7][8][9] Further studies will investigate whether these formulations can be extended to the length gauge approach, which does not have the spurious static limit issue but where the whole tensor is origin dependent. 11,28…”
Section: Discussionmentioning
confidence: 99%
“…9; we write them here in terms of the response matrix as this makes it easier to present how the origin dependence emerges (and can be removed). We have previously shown that, in general, SMVG-M ia ≠ SMVG-E ia ; however, the Sia values for each choice of perturbation are associated with the same physical process and the relative contribution of this process to the observed OR is roughly the same 9 . A feature of the Sia definition in Eq.…”
Section: Theorymentioning
confidence: 90%
See 1 more Smart Citation
“…These vectors can be visualized and superimposed to the molecular structure to determine what types of one-electron (1e) transition contribute the most to the OR. 1,[7][8][9] This vector analysis holds for the MVG approach because one can define an MVG perturbed density vector that is dotted with the vector of the paired perturbation…”
Section: Theorymentioning
confidence: 99%